A novel fish herpesvirus of Osmerus eperlanus - Jakob, Nurith Juliane; Kehm, Roland; Gelderblom, Hans R. (Virus genes, 2010)
A herpesvirus of smelt (Osmerus eperlanus) was identified by thin section electron microscopy. Degenerated cells of skin lesions located on the back fin of smelt showed either intranucleic- or cytoplasmic herpesvirus-specific structures. In the nuclei “naked” virus capsids with a diameter of about 100 nm were observed. The diameter of the complete virion including its unilaterally extended envelope ranged from 200 to 350 nm. Remarkably, in complete virions the electron-opaque tegument is completely filling the region between nucleocapsid and envelope and as another unique feature the virion shows a “comet-shape” due to a long unilateral extension of its envelope. This kind of shape had been not reported for any of herpesviruses known so far. Consequently this virus was termed herpesvirus of Osmerus eperlanus (HVOE1) or Comet herpesvirus of smelt. Due to the long time storage at the nonstandard temperature of smelt virus the biological and genomic analysis of the HVOE1 was hampered. All attempts to study host range of HVOE1 failed as no virus replication was observed, indicating that infectivity was lost or the suitable cell culture was missing. The genomic DNA of HVOE1 was analyzed by DNA restriction endonucleases.